Yasmin the ice skater ebook - Faruqi, Saadia (Yasmin, 2022)
Yasmin and her friend Emma are heading to the ice rink. But Yasmin has never skated before, and she's nervous! After a series of excuses, will Yasmin hang up her skates or find the courage to step onto the ice?